Etching Method to Create Random Speckle Pattern on Semi-Solid Cast A356 Aluminium for DIC in-situ strain measurement - Segolle, Maelle; Santos, Jorge; Kasvayee, Keivan Amiri; Jarfors, Anders E. W. (Journal of Casting & Materials Engineering, 2017)
Aluminum semi-solid casting is constantly evolving, as it offers a combination of reduced shrinkage porosity and gasentrapment defects together with high productivity and an extended die-life. The relationship between the microstructureand stress-strain behavior is not well-understood due to its non-conventional microstructure. In-situ tensile testing,combined with optical microscope and Digital Image Correlation (DIC), has been used for local strain distributionmeasuements in cast irons. The critical capability was an etching technique to generate a micro-scale random specklepattern with a sufficiently high speckle density to enable the sufficient spatial resolution of displacement and strain.The current paper focuses on the development of a pit etching procedure for the semi-solid cast A356 aluminum alloy tostudy local strain accommodation on the microstructure during tensile loading. The critical challenge of this procedurewas the generation of homogeneously distributed pits on both the primary aluminum and eutectic regions. Therefore,a heated solution used for wet-etch aluminum in microfabrication was modified as well as a process adapted to generatepits with suitable characteristics. In-situ tensile tests were performed attached to an optical microscope to recordthe microstructure and displacements during loading. DIC software was used for analysis. The procedure was validatedthrough a comparison between the resulting Young´s moduls using standard tensile testing and the DIC processon the speckle pattern generated. A good fit between the two methods for Young´s modulus was found. The spatial resolutionobtained was, however, not sufficient to fully resolve the strain gradients in the microstructure, but it did reveallarge strain variations in the microstructure.